THE ANALYSIS OF THE FOREIGN-ORIGIN WORDS IN THE EIGHTH GRADE TURKISH LANGUAGE TEXTBOOK OF PRIMARY SCHOOLS - Adem GÜRBÜZ (Fırat University, 2019)
Turkish language has borrowed vocabulary from various languages vith the effect of cultures and religious it has had since the first Kokturk epitaph works. This borrowing-process especially increased gradually vith the civilization of Uyghurs, and convertion to Islam later on. In this process, many words got into Turkish first from the eastern languages, and later from the western languages after the Tanzimat period. The foreign-origin words that got into Turkish in the purification process which begien after the Tanzimat period have been the matter of dispute with different points of view. This study deals with the foreign-origin vocabulary that exist in the Turkish language textbook of Primary schools. The foreign origin vocabulary that are analyzed in this study are from the 8th grade Turkish language textbook that is taught in the Primary schools in Bingöl. The analysis includes the origin of these vocabulary, the frequency of these vocabulary in the textbook. Mor eover, that from which languages the most borrowings are made and in which parts of the textbook these vocabulary are seen is also explained in detail in the study.